2013
DOI: 10.2214/ajr.12.9036
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Preoperative Ultrasound for Predicting pN2 or Higher Stage Axillary Lymph Node Involvement in Patients With Newly Diagnosed Breast Cancer

Abstract: Ultrasound was useful for predicting pN2 or higher axillary disease in breast cancer patients. Preoperative ultrasound assessment for staging of axillary lymph nodes might help avoid underestimation at sentinel lymph node biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 41 publications
4
46
0
1
Order By: Relevance
“…Supporting our results demonstrating correlation between AxUS nodal burden and nodal burden on final histology, Hiroyuki et al [25] found that a normal AxUS predicted the likelihood of pN0-1 disease, suggesting that SLNB would likely be sufficient for further axillary staging in these patients. Furthermore, when ≥2 abnormal nodes were noted on AxUS, this predicted pN2 disease or worse with a PPV of 82 %.…”
Section: Discussionsupporting
confidence: 87%
“…Supporting our results demonstrating correlation between AxUS nodal burden and nodal burden on final histology, Hiroyuki et al [25] found that a normal AxUS predicted the likelihood of pN0-1 disease, suggesting that SLNB would likely be sufficient for further axillary staging in these patients. Furthermore, when ≥2 abnormal nodes were noted on AxUS, this predicted pN2 disease or worse with a PPV of 82 %.…”
Section: Discussionsupporting
confidence: 87%
“…However, two previous studies focused on ultrasound's ability to discriminate between minimal and heavy axillary metastatic burden and, comparable to the present analysis, both demonstrated that patients with negative AUS had a less than 5 % prevalence of pN2-pN3 disease on final pathology. 11,12 The present study found that lobular carcinoma and CpT2 size were associated with increased likelihood of false negative AUS results. Several previous studies have examined the association of patient and tumor characteristics with false-negative AUS.…”
Section: Present Study In the Context Of Previously Published Datamentioning
confidence: 50%
“…Various attempts have been made to predict axillary LNM to avoid ALND safely [9] [10]. Several predicting models have been developed [8] [11]- [18], and many studies have been done to select the best preoperative method for predicting axillary LNM [14] [15] [17] [18]. However, the best method to do so has not been established.…”
Section: Discussionmentioning
confidence: 99%